2006
DOI: 10.1002/app.23072
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and characterization of polyaniline nanofiber doped with gadolinium chloride

Abstract: Gadolinium Chloride (GdCl 3 ) has been employed as dopant to synthesize conductive polyaniline (PANI) using chemical method. The resulting products were characterized using infrared spectroscopy, UV-vis spectra, scanning electron microscope, differential thermal analyzer, and X-ray diffraction. It was found that Gd 3ϩ can interact with PANI chains and induce changes on the properties of PANI. The addition of GdCl 3 could greatly increase electrical conductivity and crystalline degree of PANI. Changes in UV-vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The characteristic peaks appearing at 1289 and 1119 cm −1 corresponded to C—N stretching (—N—benzenoid—N—) and C N stretching (—N quinoid N—), respectively. The band appearing at 1234 and 800 cm −1 are attributed to the C—N stretching vibration and the C—H out‐of plane bending vibration, respectively . The band at 3319 cm −1 could be attributed to NH stretching mode of PANI.…”
Section: Resultsmentioning
confidence: 95%
“…The characteristic peaks appearing at 1289 and 1119 cm −1 corresponded to C—N stretching (—N—benzenoid—N—) and C N stretching (—N quinoid N—), respectively. The band appearing at 1234 and 800 cm −1 are attributed to the C—N stretching vibration and the C—H out‐of plane bending vibration, respectively . The band at 3319 cm −1 could be attributed to NH stretching mode of PANI.…”
Section: Resultsmentioning
confidence: 95%
“…By comparing PANI/PVA composite and PANI/PVA composite at different irradiation times (3, 6, 9, 12 and 15) min., it can be observed that, with increasing irradiation time, the π-π* absorption band at 230 nm and n-π* absorption band at 286nm are slightly shifted towards higher wavelength at (232, 238, 236, 236, 236) nm and (292, 296.296, 294, 296) nm respectively. This red shift which indicates that, the conjugation chain of PANI enlarged and expected to lower the absorption energy [10][11][12]. Also, there are new bands appeared at (556,564,564,562 and 564) nm for irradiation time at (3, 6, 9, 12 and 15) min.…”
Section: Uv-vis Absorption Spectroscopymentioning
confidence: 89%
“…Miscellaneous Template-Free Methods: Self-assembled PANI-NFs have been prepared by the oxidative polymerization of aniline with APS in an acidic aqueous solution in the presence of HCl [172,[204][205][206], HCl and ethanol [207], HCl and colloidal Au particles [208], H 2 SO 4 [204], o-phosphoric acid (H 3 PO 4 ) [204], H 3 PO 4 and Fe 3 O 4 nanospheres [209], HNO 3 [210], tetrafluoroboric acid [204], HClO 4 [59], selenious acid [211], hydrophilic organic acids, e.g., oxalic acid [112], citric acid [112], tartaric acid [112], and 5-sulfosalicylic acid [212], PEG [213], molybdic acid [214], and gadolinium chloride [215]. Rod-like nanostructures, as well as nano/microspheres with rod-like nanostructures pointing out to the sphere surface, have recently been prepared by the oxidation of aniline with APS in citrate/phosphate buffer (pH ¼ 3) [216,217].…”
Section: Rapid-mixing Methodmentioning
confidence: 99%